Simulated Experiment of Water-Sand Inrush across Overlying Strata Fissures Caused by Mining - Guibin Zhang; Hailong Wang; Shenglei Yan; Chuanyang Jia; Xiaoyuan Song (Geofluids)
In western region of China, the water-sand inrush across overlying strata fissures caused by mining threatens the mine safety production seriously. In order to study the development of water-sand inrush across overlying strata fissures caused by mining, a simulated test system consisted of load support bracket, laboratory module, confined water module, coal seam mining simulator, storage tank, and control system is developed. The combination of coal bearing strata in the south of Shendong mining area is looked on as the engineering background, and a series of new nonhydrophilic composite materials with lower intensity are developed to simulate the coal measure strata. The excavation of physical model can reproduce the whole process of water-sand inrush across overlying strata fissures caused by mining to the life. Under the action of mining and water pressure, after the fourth excavation, the mining-induced vertical fractures of overlying strata pass through the entire bedrock and connect the unconsolidated sand bed, which serves as pathways between the unconsolidated sand bed and working face, triggering water-sand inrush. The water pump suddenly accelerates, and the water yield suddenly increases to the extreme value of 150 L/h. The water pressure rapidly drops to 0 MPa, and a small amount of colored sand enters into the fractures of overlying strata and flows out with the water. The distribution of support pressure around the working face can be divided into 4 areas obviously, that is, the original stress area, the stress-concentrated area, the stress-released area, and the stress restoration area. Test results show that the system is stable and reliable, which have important significance for studying the formation mechanism of water-sand inrush across overlying strata fissures further.